Growth, Carcass Quality and Serum Constituents of Slow Growing Chicks as Affected by Betaine Addition to Diets Containing 1. Different Levels of Choline - Hassan, R.A.; Attia, Y.A.; El-Ganzory, E.H. (International Journal of Poultry Science, 2005)
The response of slow growing chicks to different dietary levels of choline andor betaine was investigated during the starter-grower period from 1 to 56 d of age. Therefore, a basal all-mash corn-soybean meal diet was formulated to contain 872 mg of choline based on native one. This diet was supplemented with 0, 300 and 600 mg of choline, from feed grade choline chloride (50%), which is equal to 872, 1172 and 1472 mg total choline/kg feed. Each choline level was supplemented with, 0.0, 0.072 and 0.144% betaine. Thus there were nine experimental diets; each diet was fed to 45 chicks divided equally among 5 replicates of nine unsexed chicks each. Irrespective of betaine addition, choline supplementation at 300 mg/kg diet significantly increased BWG by 3.2% and insignificantly improved FCR by 3.3% compared to unsupplemented basal diet (872 mg choline/kg diet). Choline supplementation at either medium or high level significantly increased blood serum albumin, while response to SRBC`s was linearly (P< 0.05) increased with increasing choline supplementation. Furthermore, choline at only 1172 mg/kg diet significantly decreased relative weight of abdominal fat, while increasing choline level to 1472 mg/kg diet did not affect relative weight of abdominal fat. Irrespective of choline supplementation, betaine addition at either 0.072 or 0.144% significantly improved BWG by 4.4 and 4.8%, and FCR by 4.2 and 6.1% compared to the basal diet, respectively. Betaine addition at 0.072 and 0.144% significantly increased serum total protein, albumen, and secondary response to SRBC`s, while primary responses to SRBC`s was linearly increased (P< 0.05) with increasing betaine addition. Betaine significantly decreased relative weight of abdominal fat linearly. Results indicated that betaine addition at 0.072% to 872, 1172 or 1472 mg choline- containing diet increased BWG by 3.9, 4.1 and 5.1% and improved FCR by 4.1, 4.3 and 4.8% compared to their respective controls, respectively. Also, betaine addition at 0.144% to 872, 1172 and 1472 mg/kg diet increased BWG by 5.0, 4.9 and 4.4% and improved FCR by 4.8, 4.3 and 4.1% compared to their respective controls, respectively. Betaine addition at 0.072 or 0.144% to the basal diet containing 872 mg choline resulted in similar BWG and FCR, serum total protein, albumen and primary response to SRBC`s of those fed diet containing 1172 or 1472 mg choline. In conclusion, slow growing chicks gained 13.3 g/d during 1-56 d of age required a choline level of 1172 mg/kg feed. However, choline level of 872 mg choline, which derived from native one, was adequate when dietary 0.072% betaine was added.